Preliminary evidence for genetic resistance to endoparasites in Menz and Horro lambs in the highlands of Ethiopia - Rege, J.E.O.; Tembely, S.; Mukasa, E.; Sovani, S.; Anindo, D.O.; Lahlou-Kassi, A.; Baker, R.L. (International Livestock Centre for Africa, 1996)
The Menz and Horro highland sheep breeds are being evaluated at the ILCA Debre Birhan research station in Ethiopia for between-and within-breed genetic variation for resistance to internal parasites. The experimental design involves mating, for each breed, 150 ewes with 10 rams to lamb at the beginning of the dry season (October/November) and the wet season (June/July). This paper reports data collected from birth to weaning on lambs from the first three lamb crops (i.e. born October/November 1992; June/July 1993; October/November 1993). The traits analysed were birth weight (BWT), weaning weight (WWT), packed red cell volume (PCV) recorded at weaning, logarithm transformed faecal egg count (LFEC) recorded at weaning and lamb survival from birth to weaning. The effect of both breed and lambing group was significant (P) for all traits analysed. Horro lambs were heavier at birth and at weaning, had lower PCV, higher LFEC and lower survival rate from birth to weaning than Menz lambs. There was a significant interaction of breed by lambing group for all traits except BOOT. For lamb survival, WWT and PCV the interaction took the form of varying magnitude of differences between the breeds in different lambing groups rather than any change in breed ranking. For LFEC the breed ranking changed in different groups with the Menz having higher LFEC than Horro lambs in the first lambing group, while the reverse was true in the other two lambing groups. There was no evidence from these data that the breed difference in lamb survival was due to resistance to endoparasites. There was significant additive genetic direct and maternal variance for BWT and WWT. For BWT the estimate of the direct (h2A) and maternal (h2M) heritability were 0.07±0.06 and 0.34±0.06, respectively, while for WWT the corresponding estimates were 0.04±0.05 and 0.43±0.07. For PCV and LFEC h2M was not significant and the overall heritability estimates were 0.34±0.14 and 0.32±0.13, respectively.